Production model based on Lean Manufacturing-TPM to increase the service level in a SME in the food sector - Vargas-Patroni, Arantxa; Jackson-Aguilar, Andrés; Collao-Diaz, Martin (LACCEI, 2024)
This article provides a comprehensive exploration of the challenges faced by a company operating in Peru’s competitive food industry, specifically within the "Sauces, Dressings, and Condiments" category. The selected company grapples with issues related to service levels, productivity, and efficiency, necessitating strategic interventions for improvement. With a targeted approach to address these challenges, the research proposes the implementation of Total Productive Maintenance (TPM) and Lean Manufacturing to significantly enhance the company’s operational performance, placing a particular emphasis on mitigating inefficiencies within the packaging area. Insights into the principles of these tools are provided, showcasing their potential positive impacts on operational efficiency in similar contexts. The article introduces a carefully crafted model, centered around standardized work and TPM, aimed at enhancing the company’s service levels. This model unfolds through stages, including problem analysis, tool implementation, and validation. Simulation results demonstrate a tangible potential increase in service levels from 83% to 94.2%, accompanied by notable improvements in Mean Time Between Failures (MTBF) and Mean Time To Repair (MTTR). While the achieved results fall slightly short of the initially set goals, they underscore significant progress and signal the potential for further refinement, affirming the effectiveness of Lean Manufacturing and TPM in elevating the specific company’s operational performance within the dynamic and competitive landscape of the food sector.